Work System Improvement Based NASA-TLX and SSRT to Reduce Mental Workload and Work Fatigue - Ardana, Caesar Rifqi; Iftadi, Irwan (Faculty of Industrial Technology Universitas Islam Indonesia, 2025)
Work fatigue is a critical issue in modern industries, especially where high production targets must be achieved within limited timeframes. At GM Screen Printing, growing production demands have increased mental workload, which negatively affects employee performance and health. This study, involving 11 respondents, aimed to reduce mental workload and work fatigue through improvements in the work system. Two assessment tools were employed: the NASA Task Load Index (NASA-TLX), which measures six dimensions of workload (mental demand, physical demand, temporal demand, performance, effort, and frustration), and the Subjective Self Rating Test (SSRT), which evaluates work fatigue through indicators such as reduced activity, decreased motivation, and physical fatigue. Statistical analysis revealed a significant positive correlation between mental workload and work fatigue (r = 0.604; p = 0.049; n = 11). The main contributors to mental workload were temporal demand, performance expectations, and work effort, while fatigue was primarily associated with reduced activity and physical fatigue. Based on these findings, targeted improvements are recommended, including adjusting staffing levels to alleviate time pressure, enhancing ergonomic conditions to reduce physical strain, optimizing the work environment to support sustained performance, and providing stress management training to mitigate frustration and maintain motivation.